Governance standards: A roadmap for increasing safety at care transitions. Issue 1 (January 2015) - Mitchell, Jonathan I.; Izad Shenas, Seyed Abdolmotalleb; Kuziemsky, Craig
Reducing the rate of adverse events and preventable harm associated with healthcare delivery is a policy priority across healthcare systems internationally. Care transitions or handovers in clinical care introduce risk to patients that can lead to adverse events. Building on the literature showing the impact of governing boards on the quality and safety of healthcare services, this study builds a predictive model between governance and safety at care transitions. Analysis was based on 490 Canadian healthcare organizations across six sectors of care. Organizational compliance with the Accreditation Canada Governance Standards was shown to be a predictor of organizational performance with the Medication Reconciliation Required Organizational Practice. Results indicate that among a comprehensive set of governance standards, a set of 11 central governance elements predict organizational medication reconciliation practice. Implications for healthcare leaders are discussed including the role of organizational leadership in medication reconciliation practices. The importance of a governance process cycle that encompasses board prioritization of desired goals, monitoring of performance regularly, and communicating results with stakeholders is shown.